Light Manufacturing in Zambia : Job Creation and Prosperity in a Resource-Based Economy - Dinh, Hinh T. (Washington, DC: World Bank, 2013)
This book on light manufacturing in Zambia is part of broader World Bank work on light manufacturing in Africa. The focus on light manufacturing, with its emphasis on labor-intensive economic activities, is particularly appropriate for a resource-based economy such as that of Zambia. While Zambia's recent growth has been impressive, it has not been accompanied with adequate job creation. The long-term job creation in copper production has been small; links to the rest of the economy tend to be weak as well; and the development of natural resources tends to discourage job-creating sectors such as manufacturing in any case. This book has several innovative features. First, it provides in-depth cost comparisons between Zambia and four other countries in Africa and Asia at the sector and product levels. Second, the book uses a wide array of quantitative and qualitative techniques to identify key constraints to enterprises and to evaluate differences in the performance of firms across countries. Third, it uses a focused approach to identify country-and industry-specific constraints. It proposes market-based measures and selected government interventions to ease these constraints. Fourth, it highlights the interconnectedness of constraints and solutions. For example, solving the manufacturing input problem requires actions in agriculture, education, and infrastructure. The book shows that Zambia has the potential to become regionally competitive in several light manufacturing subsectors by leveraging its comparative advantage in natural resource industries such as agriculture, livestock, and forestry. Growing the production of light manufacturing goods would allow Zambia to capture more value from its raw materials and create more jobs.